Femininity of the murderess. Feminist reading of Alexandros Papadiamantis’ Η φόνισσα - Trzaska, Nina Anna (Byzantion Nea Hellás, 2021)
The purpose of this article is an examination of femininity depicted in Papadiamantis’ Φόνισσα through the elaboration on four selected masks of Frankojannou: Mother and Daughter, Christian, Witch, Murderess. The innovative contribution lies in the application of Ardener’s model of the muted group to the society of Skiathos, deeper analysis of the cause of Hadoula’s madness as well as contestation of traditional paradigm. The feminist reading of the text concludes that Papadiamantis associates womanhood with death which returns as a reoccurring motif throughout the story. Despite the grim outcome, the novel is presented as a positive example of an androtext.